SQL server 2008 administration : real world skills for MCITP certification and beyond - Carpenter, Tom (Serious skills., 2010)
The ideal on-the-job reference guide for SQL Server 2008 database administrators. If you manage and administer SQL Server 2008 in the real world, you need this detailed guide at your desk. From planning to disaster recovery, this practical book explores tasks and scenarios that a working SQL Server DBA faces regularly and shows you step by step how to handle them. Topics include installation and configuration, creating databases and tables, optimizing the database server, planning for high availability, and more. And, if you're preparing for MCTS or MCITP certification in SQL Server 2008 admin.